Electronic money and the future of Caribbean central banks - Belgrave, Anton ([Caribbean Centre for Monetary Studies] [St. Augustine]TT, 2001)
Attempts to assess the possible implications of the emergence of privately issued e-money on central banks' ability to conduct monetary policy. Focuses particularly on the potential impact of e-money on monetary policy implementation in the micro-economies of the Caribbean.